2008
DOI: 10.1055/s-2008-1027329
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound in Diagnosis of Fractures in Children: Unnecessary Harassment or Useful Addition to X-ray?

Abstract: Ultrasound is comparable to X-ray for the detection of fractures. Ultrasound should be the first imaging method in children with trauma and nonspecific clinical signs or indistinct location of pain, followed by X-ray exams of the predefined region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
1
15

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 7 publications
(8 reference statements)
1
39
1
15
Order By: Relevance
“…48 In addition to eight articles that had not been published at that time, 20,[26][27][28]32,33,41,46 our study includes thirteen other articles not included in that review. 21,22,24,25,29,30,[34][35][36]38,41,43,44 Additional studies were possibly found as a result of a more comprehensive search strategy. Our review reaches similar conclusions, that PoCUS is a useful tool to supplement radiographs for the detection of fractures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…48 In addition to eight articles that had not been published at that time, 20,[26][27][28]32,33,41,46 our study includes thirteen other articles not included in that review. 21,22,24,25,29,30,[34][35][36]38,41,43,44 Additional studies were possibly found as a result of a more comprehensive search strategy. Our review reaches similar conclusions, that PoCUS is a useful tool to supplement radiographs for the detection of fractures.…”
Section: Discussionmentioning
confidence: 99%
“…All studies reported both the sensitivity and specificity of PoCUS, and LRs were calculated from these values when the authors did not include them in their manuscripts. Twenty-five studies 7,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][41][42][43][44] were included, ranging from 26 to 653 patients. Collectively, these studies included 2,982 patients and identified 1,200 fractures, with fracture prevalence ranging from 7% to 71% (aggregate prevalence of 40.2%).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Multiple studies show that ultrasound for fracture diagnosis has good accuracy when used by clinicians [12][13][14][15] as well as when used by radiologists. 16,17 In addition, ultrasound is well tolerated by children, even in areas of injury. 12,15 Emerging data suggest that ultrasound diagnosis of skull fractures in children is promising, 13,15,[17][18][19][20] and additional investigation of its utility is warranted.…”
mentioning
confidence: 99%
“…16,17 In addition, ultrasound is well tolerated by children, even in areas of injury. 12,15 Emerging data suggest that ultrasound diagnosis of skull fractures in children is promising, 13,15,[17][18][19][20] and additional investigation of its utility is warranted. Our principal objective was to determine the test performance characteristics for point-of-care ultrasound performed by clinicians compared with CT scan for the diagnosis of skull fractures in children.…”
mentioning
confidence: 99%